Examining accent bias towards Turkish speakers of Dutch: A speaker evaluation experiment - Van Puyvelde, Moira; Van Hoof, Sarah; Lybaert, Chloé; Plevoets, Koen (Dutch Journal of Applied Linguistics, 2023)
This contribution investigates the attitudes of Flemish first language speakers towards Turkish-Flemish speakers of Dutch as a second language. We conducted a 2 x 2 x 2 speaker evaluation experiment measuring the effects of accent (native vs. Turkish), language variety (standard vs. colloquial) and name (Flemish vs. Turkish) on attitudes vis-à-vis male speakers of Belgian Dutch. Our findings provide no consistent evidence of a negative bias vis-à-vis Turkish names in Flanders. While this result could be attributed to a social desirability bias, consistent downgrading of the Turkish accent on Superiority provides an indication of the existence of an accent bias that penalises ethnic minority accents in competence-related judgements.